2021
DOI: 10.1590/1981-6723.25720
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of uvaia nectar and evaluation of physicochemical stability during storage

Abstract: Brazilian Cerrado fruits have a great diversity of bioactive compounds, with significant relevance for fresh consumption and industrial processing. The uvaia (Eugenia pyriformis Cambess) stands out among these fruits, seeing that this species contains high phenolic compounds and ascorbic acid levels. However, its technological and nutritional potential is still little explored industrially. This research aimed to develop three uvaia nectar formulations and to evaluate its stability during 90 days of storage. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Justino et al . (2021) formulated uvaia‐based nectars exclusively, with 30–50% pulp. As the concentration increased, the acidity and ascorbic acid content increased proportionally.…”
Section: Conservation and Processing Methods Of Uvaia: Opportunities ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Justino et al . (2021) formulated uvaia‐based nectars exclusively, with 30–50% pulp. As the concentration increased, the acidity and ascorbic acid content increased proportionally.…”
Section: Conservation and Processing Methods Of Uvaia: Opportunities ...mentioning
confidence: 99%
“…Similarly, Tomaz et al (2019) found that incorporating 20-30% uvaia pulp into orange nectar significantly increased levels of ascorbic acid and phenolic compounds, with a notable improvement in microbiological stability observed with a 30% pulp addition. Justino et al (2021) formulated uvaia-based nectars exclusively, with 30-50% pulp. As the concentration increased, the acidity and ascorbic acid content increased proportionally.…”
Section: Approaches For Extraction Of Bioactive Compounds From Uvaiamentioning
confidence: 99%